O campo árido dos fraseologismos. (QUALIS B1) - Sabino, Marilei Amadeu [UNESP] (My University, 2011)
In the field of phraseological studies, it is clear that there are no strict limits able to establish accurately the various types of word combinations. There is not even a general agreement on what units are objects of study of phraseology, nor what names they should receive. Therefore, this paper aims to raise some issues related to the different terminology used by researchers in this field, which far from providing solutions to the controversial question of phraseologisms, show that terminological profusion can not only hinder scientific advancements in this field, but also indicate that much remains to be done in the area of phraseological studies.

No âmbito dos estudos fraseológicos, percebe-se que não há limites rígidos capazes de estabelecerem, com precisão, a diversidade de fraseologismos existentes. Não há, ainda, consenso sobre quais unidades são objetos de estudos da fraseologia, nem tampouco sobre as denominações que elas devam receber. Assim, este artigo objetiva levantar algumas questões relacionadas a diferentes denominações terminológicas empregadas por pesquisadores desse campo, as quais, longe de oferecer soluções à polêmica questão dos fraseologismos, demonstram que essa profusão terminológica pode não só atrapalhar os avanços científicos nesse domínio, como também sinaliza que ainda resta muito a ser feito na Área dos estudos fraseológicos.
Keywords: Fraseologismos; Phraseologisms; collocations; idioms